Plasma exosomes exacerbate alcohol- and acetaminophen-induced toxicity via CYP2E1 pathway - Rahman, Mohammad A. (Sci Rep, 2019)
Cellular CYP2E1 is well-known to mediate alcohol- (ALC) and acetaminophen- (APAP) induced toxicity in hepatic and extra-hepatic cells. Although exosomes have been gaining importance in understanding mechanism of intra- and inter-cellular communication, the functional role of drug metabolizing cytochrome P450 (CYP) enzymes in human plasma exosomes are yet to be explored. In our previous study, we reported that human plasma-derived exosomes contain substantial level of functional CYP2E1. In the current project, we investigated the potential role of plasma exosomal CYP2E1 in mediating ALC- and APAP-induced toxicity. We treated hepatic and extra-hepatic (monocytic) cells with exosomes ± ALC/APAP. We observed that the plasma exosomes containing CYP2E1 cargo further exacerbate ALC- and APAP-induced toxicity in both hepatic and monocytic cells. Further, both exosomes- and ALC/APAP-induced toxicity was reduced/abolished by a selective inhibitor of CYP2E1 enzyme activity (diallyl ether). However, only ALC-, but not exosome-induced toxicity was reduced/abolished by CYP2E1 siRNA. These findings suggest that ALC/APAP-induced toxicity in the presence of exosomes are mediated, at least in part, by CYP2E1 enzyme. To validate these in vitro findings, we characterized plasma exosomal contents in a binge-drinking animal model and their effect on ALC/APAP-induced toxicity in monocytic cells. Our results showed that ALC exposure caused a significant induction of the plasma exosomal CYP2E1 level in a binge drinking murine model. These exosomes containing increased levels of CYP2E1 caused significant toxicity in monocytic cells compared to exosomes derived from control mice. Overall, our results showed an important role of exosomal CYP2E1 in exacerbating ALC- and APAP-induced toxicity. The study is significant in terms of understanding the role of exosomal CYP2E1 in cell-cell interactions, and their effects on drug-induced toxicity.